Combined oral contraceptives: evolution of the relationship benefit/risk - O. S. Alyautdina (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Currently, more than 100 million women worldwide use combined oral contraceptives. Risk/benefit ratio of this group of drugs over the half-century history is largely changed in the direction of safety. The factors that increase the safety of this group of drugs, as well as the main risk factors are discussed.